Hyperbaric oxygen therapy for late radiation-induced tissue toxicity: prospectively patient-reported outcome measures in breast cancer patients. Issue 1 (December 2016) - Teguh, David; Bol Raap, René; Struikmans, Henk; Verhoef, Cees; Koppert, Linetta; Koole, Arne; Huang, Yadi; van Hulst, Rob
Abstract Introduction This study examines patient reported outcome measures of women undergoing hyperbaric oxygen treatment (HBOT) after breast-conserving therapy. Method Included were 57 women treated with HBOT for late radiation-induced tissue toxicity (LRITT) referred in the period January 2014-December 2015. HBOT consisted of (on average) 47 sessions. In total, 80 min of 100 % O2 was administered under increased pressure of 2.4 ATA. Quality of life was assessed before and after treatment using the European Organization for Research and Treatment of Cancer (EORTC) QLQ-BR23, and a NRS pain score. Results Fifty-seven women were available for evaluation before and after treatment. Before HBOT, patients had severe complaints of pain in the arm/shoulder (46 %), swollen arm/hand (14 %), difficulty to raise arm or move it sideways (45 %), pain in the area of the affected breast (67 %), swollen area of the affected breast (45 %), oversensitivity of the affected breast (54 %), and skin problems on/in the area of the affected breast (32 %); post HBOT, severe complaints were still experienced in 17, 7, 22, 15, 13, 15, and 11 % of the women, respectively. Differences were all significant. The NRS pain score improved at least 1 point (range 0–10) in 81 % of the patients (p  < 0.05). Conclusion In these breast cancer patients treated with HBOT for LRITT, the patient-reported outcomes were positive and improvements were observed. HBOT was a well-tolerated treatment for LRITT and its side-effects were both minimal and reversible.